The Marvel Studios phenomenon inside a transmedia universe - Flanagan, Martin; Livingstone, Andrew 1987-; McKenny, Mike (New York Bloomsbury Academic, 2017)
"The Marvel Studios Phenomenon evaluates the studio's identity, as well as its status within the structures of parent Disney. In a new set of readings of key texts such as Captain America: The Winter Soldier, Guardians of the Galaxy and Agents of S.H.I.E.L.D., the thematics of superhero fiction and the role of fandom are considered. The authors identify milestones from Marvel's complex and controversial business history, allowing us to appraise its industrial status: from a comic publisher keen to exploit its intellectual property, to an independent producer, and latterly, successful subsidiary of a vast entertainment empire. As it drives the process whereby large-scale cinematic practice encounters a converged entertainment age, what kind of organization is Marvel Studios? How does it co-ordinate a transmedia storyworld to the satisfaction of niche fan communities as well as a popular audience?"-- Provided by publisher.
Introduction: The Road to Marvel Studios -- 1. 'Films Lead Policy': Marvel's Industrial (R)evolution and the Birth of a Studio -- 2. An Organization of Storytellers: The Marvel Story, According to Marvel -- 3. 'Doth Mother know you weareth her drapes?': The Genre Tactics of Marvel Studios -- 4. Captains America -- 5. Teams/Screens -- 6. Star-Lord, Who?: Guardians of the Galaxy - Raiding the 'B-List' for New -- Legends -- 7. 'A Little Old-Fashioned: Marvel Studios and Pixar -- 8. Tie-ins, Tie-ups and Let-downs: Marvel's Transmedia Empire -- Conclusion -- Appendix: Timeline.
Includes bibliographical references (pages 244-261) and index.
Keywords: Marvel Studios -- History; Motion picture industry -- United States -- History